Molecular Characterization of Neem Rhizosphere Bacteria as A Nitrogen Fixer Isolated from The Dry Land of East Lombok - Umami, Rizal; Zulkifli, Lalu; Bahri, Syamsul; Mahrus; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Bacteria have an important role in providing essential nutrients for plants in dry land through various beneficial working mechanisms. One of the main mechanisms is the involvement of bacteria in nutrient cycles, such as the nitrogen cycle. The aim of this research was to determine the type and ability of bacteria in the rhizosphere of neem (Azadirachta indica) to fix nitrogen. The method used in this research is an exploratory descriptive type. The results of the isolation carried out from the rhizosphere of neem (Azadirachta indica) taken from the East Lombok area of Jerowaru sub-district, 5 samples were obtained with the code LO, where 2 isolates had the ability to fix nitrogen, namely LO3 and LO4. This is proven by using NFB media where there is a change in the color of the media from green to blue, and quantitatively using a spectrophotometer with results of 1,112 ppm and 2,156 ppm, respectively. The results of the molecular identification of the potential bacteria, namely LO4, using the BLAST method at the GenBank data base (NCBI), show that LO4 is the closest relationship to the species Lysinibacillus fusiformis strain SMC303. The results above show that rhizobacteria isolated from neem have the potential to be developed as a biofertilizer that can be applied to future cultivated plants.